2021
DOI: 10.1186/s13756-021-00907-w
|View full text |Cite
|
Sign up to set email alerts
|

Foley catheter with noble metal alloy coating for preventing catheter-associated urinary tract infections: a large, multi-center clinical trial

Abstract: Background Catheter-associated urinary tract infections (CAUTI) are among the most frequent healthcare-associated infections in the world. They are associated with increased mortality, prolonged hospital stay and increased healthcare costs. The objective of this study was to evaluate the efficacy of the noble metal alloy (NMA) coated BIP Foley Catheter in preventing the incidence of symptomatic CAUTI in a large cohort of patients in India. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…An interesting study reported leaching of metals into urine was minimal or undetectable . In one urine sample, 0.2 μg/L silver was detected, which is 4% of the permitted daily exposure for drugs …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…An interesting study reported leaching of metals into urine was minimal or undetectable . In one urine sample, 0.2 μg/L silver was detected, which is 4% of the permitted daily exposure for drugs …”
Section: Resultsmentioning
confidence: 96%
“…However, the CAUTI risk was lower in the coated group among patients requiring catheterization for longer than 14 days . A coating comprised a palladium, gold, and silver alloy layer and a hydrogel outer layer significantly decreases the incidence of CAUTI . An interesting study reported leaching of metals into urine was minimal or undetectable .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The galvanic effect of noble metal alloys creates a microcurrent that reduces the formation of bacterial biofilm, and thus colonization of the ETTs, and subsequent respiratory infection [ 12 ]. Metal-coated urinary catheters have been on the market since 1995 and have been tested in a large number of clinical studies; results have demonstrated a reduction in urinary tract infections and antibiotic use [ 13 18 ]. Although there is substantial clinical evidence demonstrating that the NMA coating can reduce the infection rate related to other medical devices such as urinary catheters, more data on the efficacy of NMA-coated ETTs on VAP are needed.…”
Section: Introductionmentioning
confidence: 99%